General Guidelines for Submission of Original Research Papers - R. T. Saygitov (Union of pediatricians of Russia, 2015)
This is an abridged version of the article that was published in Voprosy sovremennoi pediatrii - Current Pediatrics. 2015;14(3):425-432. doi: 10.15690/vsp.v14i3.1382